Modified approach for keratinized tissue augmentation in multiple teeth - Mayara Terenzi; Suzane Cristina Pigossi; Luana Carla Pires; Joni Augusto Cirelli; José Eduardo Sampaio (Wolters Kluwer Medknow Publications, 2017)
This case report demonstrated a modified technique of free gingival graft (FGG) aiming to increase keratinized attached tissue in large recipient areas. A FGG to increase the amount of attached gingival tissue, facilitate oral hygiene, and prevent further clinical attachment loss was realized in two patients. Because the extensive recipient area, a modified technique was performed to obtain a smaller graft of the donor area. A template of the graft was made about 25%-30% smaller than the total recipient area. After graft removal, interspersed incisions were made in the upper and lower edges of it. After 9-24 months of follow-up, the final width of the keratinized tissue was 4.0-4.4 times larger in comparison to initial clinical condition. In conclusion, this FGG technique can be considered an alternative to gain sufficient amount of keratinized gingival tissue using a smaller graft.